ETHICAL PROBLEMS OF REALIZATION OF CALLING OF A PERSON - Muliarchuk, Yevhen I. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
The article researches ethical problems of realization of human calling. On the basis of ideas of the ethics of E. Levinas and their interpretations the author proves the importance of ethical dimension of evaluation of calling as a way of self-actualization of a personality. The purpose of the study is to determine of the conditions and requirements for understanding of calling by personality. However, from the ethical point of view those conditions and requirements appeared to be independent from the individual aims and visions of calling. Therefore, reveals itself the transcendence of the purpose of calling, devotion of a person to over-personal aims and values. The research analyzes the interrelations between the ideas of calling and mission or assignments of a man in the world. The ethical problem presents also the realization of the ethical obligations versus desires and will of calling. The article researches the problem of the purpose of life related to individual understanding of calling. The other issue of the study is the topic of a highest good as the aim and ethical dimension for calling. The theme of destiny and predestination researched as relevant for the experience of calling as well as the phenomenon of gift. Calling is a realization of given to a person and of his or her gifts. For the conclusion was determined the multidimensional character of values of human calling. In the essence of this phenomenon revealed the combination of personal and transcendent, over-personal motives. There is a hierarchy of levels of good in the experience of calling. The person must be able to build up and understand those levels by means of ethical thinking in order to realize calling in the life. There could not be an irresponsible calling of a person. It has to be a correlation of calling with responsibility to family, society and the world of higher ethical values.